Sclerostin Immunoreactivity Increases in Cortical Bone Osteocytes and Decreases in Articular Cartilage Chondrocytes in Aging Mice. (March 2016) - Thompson, Michelle L.; Jimenez-Andrade, Juan Miguel; Mantyh, Patrick W.
Sclerostin is a 24-kDa secreted glycoprotein that has been identified as a negative modulator of new bone formation and may play a major role in age-related decline in skeletal function. Although serum levels of sclerostin markedly increase with age, relatively little is known about whether cells in the skeleton change their expression of sclerostin with aging. Using immunohistochemistry and confocal microscopy, we explored sclerostin immunoreactivity (sclerostin-IR) in the femurs of 4-, 9-, and 24-month-old adult C3H/HeJ male mice. In the femur, the only two cell types that expressed detectable levels of sclerostin-IR were bone osteocytes and articular cartilage chondrocytes. At three different sites along the diaphysis of the femur, only a subset of osteocytes expressed sclerostin-IR and the percentage of osteocytes that expressed sclerostin-IR increased from approximately 36% to 48% in 4- vs. 24-month-old mice. In marked contrast, in the same femurs, there were ~40% fewer hypertrophic chondrocytes of articular cartilage that expressed sclerostin-IR when comparing 24- vs. 4-month-old mice. Understanding the mechanism(s) that drive these divergent changes in sclerostin-IR may provide insight into understanding and treating the age-related decline of the skeleton.